2023
DOI: 10.1038/s41598-023-31625-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nitrogen doped TiO2/Fe2O3 nanostructures for photocatalytic oxidation of methanol based wastewater

Abstract: An important industrial process that often occurs on the surface of a heterogeneous catalyst using thermochemical or photochemical could help in the oxidation of methanol-based wastewater to formaldehyde. Titania-based photocatalysts have drawn a lot of interest from scientists because they are a reliable and affordable catalyst material for photocatalytic oxidation processes in the presence of light energy. In this study, a straight-forward hydrothermal method for producing n-TiO2@α-Fe2O3 composite photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The solvothermal synthesis of nitrogen-doped TiO 2 and Fe 2 O 3 nanocomposites yielded photocatalysts with enhanced activity owing to the formation of a heterojunction between nitrogen-doped TiO 2 and Fe 2 O 3 . The nanocomposite absorbed light at a higher rate compared to the TiO 2 alone and resulted in the nearly complete oxidation of methanol [65] Solvent-based multi-doping strategies had also been explored, aiming to enhance the optoelectronic properties of TiO 2 . These strategies involve doping TiO 2 with non-metals (nitrogen, carbon, and sulphur) and metals (e.g., iron) using the sol-gel synthesis method.…”
Section: Photocatalysts Doped With Non-metalsmentioning
confidence: 99%
“…The solvothermal synthesis of nitrogen-doped TiO 2 and Fe 2 O 3 nanocomposites yielded photocatalysts with enhanced activity owing to the formation of a heterojunction between nitrogen-doped TiO 2 and Fe 2 O 3 . The nanocomposite absorbed light at a higher rate compared to the TiO 2 alone and resulted in the nearly complete oxidation of methanol [65] Solvent-based multi-doping strategies had also been explored, aiming to enhance the optoelectronic properties of TiO 2 . These strategies involve doping TiO 2 with non-metals (nitrogen, carbon, and sulphur) and metals (e.g., iron) using the sol-gel synthesis method.…”
Section: Photocatalysts Doped With Non-metalsmentioning
confidence: 99%
“…Thermal pretreatment is helpful for the growth of hydrogen-producing bacteria after suppressing the activity of methanogens [29]; however, in the chemical treatment processes that were treated by acetylene, iodopropane, methanol and bromo ethane sulfonic acid (BESA), these served as inhibitors and very toxic for bacteria [30]. Some researchers have demonstrated that alkaline pretreatment methods outperform acidic pretreatment techniques as a pretreatment method for anaerobic sludge [31].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the deposition of Fe 2 O 3 on TiO 2 nanoparticles improved the absorption of visible light and the photocatalytic activity for the breakdown of organic pollutants in aqueous solution [19]. Photogenerated electron-hole pairs could be separated more easily if the Fermi energy levels of TiO 2 and Fe 2 O 3 aligned and an internal electric field was created hence increasing the photocatalytic performance [26].…”
Section: Introductionmentioning
confidence: 99%